การประเมินความสามารถในการรับแรงแผ่นดินไหวของโครงสร้างผนังอิฐรับน้ำหนัก ด้วยวิธีโต๊ะที่ปรับเอียง - Jinwuth, Watcharin (Naresuan University Journal: Science and Technology (NUJST); Vol 19 No 2 (2011): May-August 2011, 2014)
Unreinforced adobe or mud-brick structures are weak when subjected to seismic forces. These types of buildings used in many locations throughout the world suffer severe damage from seismic forces and cause a vast number of deaths. There has been limited research on the effect of seismic forces on adobe structures as the research equipment is expensive and requires specialist research personnel to undertake meaningful investigations. Most seismic research on adobe structures has been undertaken in the developed countries that are able to afford the specialized research equipment and staff. This paper presents the seismic experiments undertaken to evaluate the results of the performance of circular adobe structure failure utilising a simple static-tilt-table. The static tilt-table testing was compared to test results using a dynamic shake-table. Two small-scale circular models (1:3 scale) of unreinforced adobe structures were built, tested on a static tilt-table testing and a dynamic shake-table. The results confirmed that the results from the tilt-table testing coincided with the results of the dynamic shake-table. In addition, the failure of circular adobe buildings assisted to predict the failure mechanism of unreinforced adobe or mud-brick structures in the future.
Keywords: บ้านดิน, อิฐดินดิบ, ต้านแผ่นดินไหว, บ้านทรงกลม, โต๊ะที่ปรับเอียง, Adobe construction, mud-brick, earthquake resistance, circular building, tilt table test